PENERAPAN SANKSI PIDANA TERHADAP MUCIKARI PROSTITUSI MENURUT KITAB UNDANG-UNDANG HUKUM PIDANA - Bulan Agustina Nada (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTIndonesian society is known as an ethical and moral religious society, but it cannot be denied that the problem is that there are still many crimes of pimps still rife. Pimping is an act of facilitating a person's obscene or adultery in exchange for money and making this act a livelihood. The act of pimping that deviates from the provisions of the law and has violated the norm is a criminal act.The type of research used in this paper is normative legal research with a law approach and several primary, secondary and tertiary legal sources.The act of pimping that facilitates obscene acts by other people with other people and profiting from obscene acts has been regulated in the Criminal Code, that the act of taking advantage of the obscene acts of a woman and making it a livelihood is a criminal act of pimping and whoever commits the crime of pimping will be subject to Article 296 and Article 506 of the Criminal Code in the form of a criminal sanction of imprisonment for a maximum of one year. The provisions for the crime of pimping are also regulated outside the Criminal Code, this aims to anticipate all types of actions in the process, method or all forms of exploitation that will occur.The factors that caused pimps to offer prostitutes services at guesthouses after the closure of lokalisasis were due to economic needs, because they were used to getting lots of money quickly and easily from taking advantage of offering the services of commercial sex workers, pimps carried out their actions in guesthouses in Pasuruan secretly. hide to earn money from peddling commercial sex workers.Keywords: application, criminal sanctions, pimping.